Recent progress of thick tungsten coating prepared by chemical vapor deposition as the plasma-facing material. (28th October 2021) - Chen, Z.; Li, Y.; Cheng, L.; Wang, Z.; Lian, Y.; Liu, X.; Feng, F.; Wang, J.; Tan, Y.; Morgan, T.W.; Lu, G.H.; Ye, X.; et al.
Abstract: Chemical vapor deposition (CVD) is a promising technique for the preparation of W-based plasma-facing materials (PFMs). An overview of the microstructure, chemical composition, thermal conductivity, thermal stability, thermal shock performance under disruption-like and edge localized mode-like transient heat load, and neutron irradiation performance of CVD-W has been given in our previous work. However, for fusion applications, additional properties need to be assessed. To this end, deuterium (D) permeability, D plasma irradiation performance, and thermal fatigue resistance of CVD-W were investigated in this work. The results showed that the D permeability of CVD-W in the temperature range of 973–1173 K was larger than that of the commercial pure W, which was related to the columnar grain structure of CVD-W. Additionally, both CVD-W and commercial pure W were exposed to D plasma up to a fluence of 1 × 10 26  m −2 . Compared to commercial pure W, CVD-W exhibited a mitigated blistering behavior and lower D total retention, which could be attributed to its strong [001] crystallographic texture along the thickness direction and a lower number of defect density (e.g. grain boundaries). CVD-W and commercial pure W were also exposed to steady-state and transient heat load simultaneously, leading to a base surface temperature and surface temperature increase of about 953–1473 K and 250–300 K, respectively. A strong grain orientation dependence of the surface degradation induced by the combined heat load has been found. Consequently, CVD-W exhibited a much more uniform plastic deformation than pure W, and no surface cracks along grain boundaries were observed in CVD-W. Finally, the industrial-scale production of CVD-W-based PFMs and mockups was demonstrated. This work paves the way for the fusion applications of thick CVD-W coatings.